2011
DOI: 10.1292/jvms.11-0130
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Cyclooxygenase-2 in the Endometrium of Gilts with Different Stages of Endometritis

Abstract: ABSTRACT. The present study determined the association among the expression of COX-2, stages of endometritis, and types and number of local immune cells infiltrating into the gilts' endometrium. The uterine tissues from 24 Landrace x Yorkshire gilts identified as acute endometritis (n=7), chronic endometritis (n=7), and normal endometrium (n=10) were included. The tissues were prepared for both histological and immunohistochemical investigations. The immunoexpression of COX-2 in every layer of the gilts' endom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 27 publications
0
8
0
1
Order By: Relevance
“…Pseudopregnancy was defined as the absence of estrus maintained from Day 17 to the day of PGF 2α treatment (Day 38, 45, 52, or 59), as described previously (Noguchi et al, 2011). Body condition was assessed both by visual appraisal (Coffey et al, 1999; Pairis‐Garcia & Moeller, 2017) and by measuring the back‐fat thickness using an ultrasound scanner (Anyscan; Global Pig Farm Co., Ltd., Shibukawa, Japan) (Charette et al, 1996; Roongsitthichai & Tummaruk, 2014) on Day 10. All animals were fed a gestational diet (CP‐TDN; 13.0%–72.0%) during the experimental period.…”
Section: Methodsmentioning
confidence: 99%
“…Pseudopregnancy was defined as the absence of estrus maintained from Day 17 to the day of PGF 2α treatment (Day 38, 45, 52, or 59), as described previously (Noguchi et al, 2011). Body condition was assessed both by visual appraisal (Coffey et al, 1999; Pairis‐Garcia & Moeller, 2017) and by measuring the back‐fat thickness using an ultrasound scanner (Anyscan; Global Pig Farm Co., Ltd., Shibukawa, Japan) (Charette et al, 1996; Roongsitthichai & Tummaruk, 2014) on Day 10. All animals were fed a gestational diet (CP‐TDN; 13.0%–72.0%) during the experimental period.…”
Section: Methodsmentioning
confidence: 99%
“…Both COX-1 and COX-2 are expressed in the uterine epithelium at different times in early pregnancy [14], whilst COX enzymes are also known to be involved in endometrial pathology [15]. Animal studies have demonstrated that the immunoexpression of COX-2 was found to be strongest in endometrium with acute endometritis compared with normal endometrium or chronic endometritis [16]. In addition, COX-2 expression has been found to be an independent prognostic factor in uterine leiomyosarcomas [17].…”
Section: Introductionmentioning
confidence: 99%
“…It has also been found that both anti‐Müllerian hormone (AMH) and IGF‐I concentrations at 90–100 days of age were higher in earlier maturing gilts compared to later maturing gilts (Am‐in et al, 2020; J. L. Patterson et al, 2010). An increase in AMH potentially reflects superior ovarian function while IGF‐I may enhance the senitization of gilt ovaries to boar stimuli (Kingsbury & Rawlings, 1993; Roongsitthichai, Cheuchuchart et al, 2013; Roongsitthichai, Koonjaenak et al, 2013). These findings indicate a close relationship between the growth performance of the gilts and puberty attainment.…”
Section: Gilt Managementmentioning
confidence: 99%